Digitalization of the educational process of training future engineers-teachers: theoretical aspectʺ - Sazhko, H. (Problems of Engineer-Pedagogical Education, 2021)
The article provides an overview of the state of the problem of digitalization of the educational process in Ukraine. Digitalization of the educational process is a requirement of the present; it is a modern condition for the existence of an education system that prepares a competitively capable specialist of a new formation with not only professional Hard skills and flexible Soft skills, but also modernly necessary Digital skills. Of course, this was confirmed by the most difficult situation during the coronavirus pandemic: the digital transformation of education is a necessity. Based on the research of scientists, both domestic and foreign, who dealt with this problem, taking into account the trends in the development of education in European countries and the requirements of a modern employer, the author justifies the complex use of information and communication technologies in the educational process achieved through the development and use of digital resources for educational purposes that meet the needs of the educational process as well as the characteristics of the content, methods and forms of education. Topical problems have been highlighted and the task of digitalization of education has been analyzed; concepts in this context have been researched and refined; a list of components of the complex of digital educational resources has been developed, which will make it possible to develop a digital information and educational environment for the modernization of the educational process. Further studies of this issue provide for the introduction of digital educational resources into the educational process of training engineers-teachers at Ukrainian Engineering Pedagogics Academy, analysis of the impact of digital educational resources on the quality of organization and conduct of the educational process, assessment of the effectiveness of the implementation of digital educational resources in the educational process, namely, the introduction of digital educational resources into the modern educational process as general tools (text editors, presentations, other "office applications"), as professional pedagogical tools (a system for forming the information space of an educational institution, a system for creating educational and methodological complexes with digital components), as subject tools (a virtual laboratory, a computer-aided design training system).